Representasi krisis lingkungan dalam lirik lagu Speak Up: Sebuah kajian ekokritisisme punk - Muhammad Fakhran al Ramadhan (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2026)
Environmental art is used as a mechanism to engage awareness in building environmental understanding and music provides some affective components of environmental education – emotions, values, and motivations driving pro-environmental behavior. Punk rock creates a sense of community and awareness through the lyrics. It is no longer about resistance to rigid, feudal systems and criticism of authoritarians, but also moves in responding to environmental issues, which is an interesting study to explore. This study aimed to explore how the ecological perspective in punk music by looking at the Jakarta punk band called Speak Up in responding to environmental issues. The initial analysis of 3 Speak Up songs; Suara Bumi, Balada Tanah Merah, and Puisi Bumi are to be analyzed. Based on literature review, theoretical basis and data obtained from observation and documentation of Ecological Perspective, the writer found that the disharmonic relationship between human and nature that showed ecological matters. Ecological Perspective is a way to understand how history, justice, and power intersect with any form of knowledge, and in this context how the lyrics deal with environmental issues and urban environmental injustices. Key Words: Environmental issues, Music Education, Punk, Ecological Perspective